Frontmatter [Front Cover, Editorial Team, Indexing, and Table of Contents] - Purwanto, L.M.F (Universitas Katolik Soegijapranata, 2023)
Frontmatter [Front Cover, Editorial Team, Indexing, and Table of Contents]